Clinical applications and diagnostic research of GFAP and NfL in MS and NMOSD: a meta-analysis - XueJuan Lin; JingYi Tong; WenJing Wu; XiaoFeng Pan (BMC Immunology)
Abstract Objective The aim of this study was to evaluate the diagnostic value of glial fibrillary acidic protein (GFAP) and neurofilament light chain (NfL) levels in multiple sclerosis (MS) and optic neuromyelitis optica spectrum disorders (NMOSD) and their relationship with disease prognosis by Meta-analysis, and to explore their potentials in early diagnosis of the disease and monitoring of its course. Methods We systematically searched China National Knowledge Infrastructure (CNKI), VIP database, Wanfang database, PubMed, Wiley online library, and web of science databases for relevant literature on GFAP in neuroimmune diseases, and the time limit for searching was from inception to December 1, 2024, and two evaluators independently assessed all the studies. Two evaluators independently assessed the quality of all the studies, evaluated the data in detail according to the criteria of risk of bias, and performed Meta-analysis using RevMan 5.4.1 software and STATA 18. Results Through literature screening, 12 studies were finally included, involving a total of 1731 participants, of which 871 were in the control group and 869 were in the experimental group. Meta-analysis results showed that GFAP levels in MS patients were significantly higher than those in healthy control groups [MD = 0.98, 95% CI (0.70, 1.25), P < 0.0001]; NfL levels were also significantly higher than controls [MD = 0.76, 95% CI (0.06, 1.46), P = 0.03]. In patients with optic neuromyelitis optica spectrum disease (NMOSD), GFAP levels were significantly higher than controls [MD = 0.97, 95% CI (0.03, 1.91), P = 0.04]; NfL levels were also significantly higher than controls [MD = 0.24, 95% CI (0.02, 0.46), P = 0.03]. Analysis of different disease stages showed that compared with healthy controls, GFAP levels were significantly elevated in patients with MS in the deteriorating phase [MD = 2.38, 95% CI (1.40, 3.37), P < 0.0001], in the active phase [MD = 2.01, 95% CI 0.20, 3.82), P = 0.03], and in the remission phase at a lower level of elevated GFAP levels [MD = 1.33, 95% CI (0.20, 2.46), P = 0.02]. For GFAP survival analysis in MS patients, the results showed no statistical significance [HR = 1.78, 95% CI (0.47, 6.66), P = 0.39]. Conclusion The levels of GFAP and NfL in MS and NMOSD patients were significantly higher than those in healthy controls. GFAP levels demonstrate a progressive decline correlating with MS disease activity—from exacerbation through active to remission phases—yet remain persistently elevated compared to controls. These findings indicate its potential utility for MS diagnosis and disease monitoring.